Tomographic fluorescence lifetime multiplexing in the spatial frequency domain - Kumar, Anand T. N. (Optica, 2018)
The ability to simultaneously recover multiple fluorophores within biological tissue (multiplexing) can have important applications for tracking parallel disease processes in vivo. Here we present a novel method for rapid and quantitative multiplexing within a scattering medium, such as biological tissue, based on fluorescence lifetime contrast. This method employs a tomographic inversion of the asymptotic (late) portion of time-resolved spatial frequency (SF) domain measurements. Using Monte Carlo simulations and phantom experiments, we show that the SF-asymptotic time domain (SF-ATD) approach provides a several-fold improvement in relative quantitation and localization accuracy over conventional SF-time domain inversion. We also show that the SF-ATD approach can exploit selective filtering of high spatial frequencies to dramatically improve reconstruction accuracy for fluorophores with subnanosecond lifetimes, which is typical of most near-infrared fluorophores. These results suggest that the SF-ATD approach will serve as a powerful new tool for whole-body lifetime multiplexing.